Special and differential treatment for small and vulnerable countries based on the situational approach - Leal, Werner Corrales; Baritto, Felipe; Mohan, Sarah A. (ICTSD Programme on Competitiveness and Sustainable Development issue paper, 2007)
Beyond the general constraints on trade and competitiveness affecting nearly all developing countries, a special class of concerns applies more specifically to the so-called Small and vulnerable Economies (SVEs). Small economies usually depend more on international trade than other countries and are more exposed to risks resulting from trade-related external shocks. In addition, many of them have encountered disasters related to natural hazards with increasing frequency and impact.